(untitled) (Journal of the College of Basic Education, 2022)
This research deals with the importance of Egypt in the Crusades, which is governed by the Fatimid caliphate. In fact, the perception of the past and its representation is a matter that faces difficulties, not only in conflicting news and its scarcity, but in rewriting history because it is primarily a political action. Therefore, writing about Egypt and its importance before the caliphate The Fatimids and prior to the Crusades are very important because it will touch, in one way or another, on their internal situationIn which the caliphate had no role in it because the aesthetic state had taken control of all the capabilities of the state politically, economically and militarily, and the Fatimid caliph was not at that stage except as the Abbasid caliphs were in Baghdad under the influence of the Buyids and the Seljuks, and all of this began in the year (466 AH / 1074 AD)